The Health Services Federation of Great Britain (leaflet) (1938)
1938 1938 1930s 5 pages HEALTH SERVICES FEDERATION OF GREAT BRITAIN. I desire to become a Member of the Health Services Federation of Great Britain. My employment is as follows :— Office held Name of Hospital, or Institution (if any) Professional qualifications (if any) Employing authority Private address Please be good enough to direct this enquiry to the appropriate organisation. Signed Date For Central Office use only. Received Refer to 292/54.73/2/5